2023
DOI: 10.3390/app13127209
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ground Reaction Forces, Foot Positions and Type of Clubs Used in Golf: A Systematic Review and Meta-Analysis

Abstract: Background: Despite the growing interest in golf, the impact of motion control strategy on golf performance may be uncertain. A network meta-analysis was conducted to investigate the relationships between ground reaction force (GRF), foot positions, and club types in golf and determine whether different clubs have a different impact when swinging. Methods: Three databases were searched from the time of inception to March 2023. Eligibility criteria included studies that provided data using a driver to swing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Different types of clubs can also cause different levels of leg stiffness. Studies have reported that the horizontal reaction force created by the lead foot or the trail foot is greater when a driver is used instead of a 6-iron club ( Peterson et al, 2016 ; You et al, 2023 ). However, iron clubs, which typically have shorter and heavier shafts than do wooden clubs, prioritize precision for landing the ball on the green over maximizing shot distance.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of clubs can also cause different levels of leg stiffness. Studies have reported that the horizontal reaction force created by the lead foot or the trail foot is greater when a driver is used instead of a 6-iron club ( Peterson et al, 2016 ; You et al, 2023 ). However, iron clubs, which typically have shorter and heavier shafts than do wooden clubs, prioritize precision for landing the ball on the green over maximizing shot distance.…”
Section: Introductionmentioning
confidence: 99%
“…In the fields of rehabilitation and sports, analyzing ground reaction forces (GRFs) and ground reaction moments (GRMs) offers advantages in assessing the risk of musculoskeletal disorders and evaluating physical performance [1,2]. To address the challenges associated with the complexity of recording GRFs and GRMs, previous studies have developed simplified measurement techniques that do not require a force plate.…”
Section: Introductionmentioning
confidence: 99%